Naming ability in patients with mild to moderate Alzheimer’s disease: what changes occur with the evolution of the disease? (Clinics, 2015)
OBJECTIVES: Naming deficit is a linguistic symptom that appears in the initial phase of Alzheimer’s disease, but the types of naming errors and the ways in which this deficit changes over the course of the disease are unclear. We analyzed the performance of patients with Alzheimer’s disease on naming tasks during the mild and moderate phases and verified how this linguistic skill deteriorates over the course of the disease. METHODS: A reduced version of the Boston Naming Test was administered to 30 patients with mild Alzheimer’s disease, 30 patients with moderate Alzheimer’s disease and 30 healthy controls. Errors were classified as verbal semantic paraphasia, verbal phonemic paraphasia, no response (pure anomia), circumlocution, unrelated verbal paraphasia, visual errors or intrusion errors. RESULTS: The patients with moderate Alzheimer’s disease had significantly fewer correct answers than did both the control group and the group with mild Alzheimer’s disease. With regard to the pattern of errors, verbal semantic paraphasia errors were the most frequent errors in all three groups. Additionally, as the disease severity increased, there was an increase in the number of no-response errors (pure anomia). The group with moderate Alzheimer’s disease demonstrated a greater incidence of visual errors and unrelated verbal paraphasias compared with the other two groups and presented a more variable pattern of errors. CONCLUSIONS: Performance on nominative tasks worsened as the disease progressed in terms of both the quantity and the type of errors encountered. This result reflects impairment at different levels of linguistic processing.